Determinants Of Economic Loss Of Village Credit Institutions and Their Policies - Ni Nyoman PADMAWATI (Indonesia Strategic Sustainability, 2021)
This study aims to examine several factors that influence the bankruptcy of LPD in Buleleng Regency; the factors in question are legal protection, management competence, good corporate governance, the active role of citizens and the role of internal supervisory bodies. Research approach with quantitative methods. This study used a questionnaire method with 63 respondents, namely LPD managers in the sub-districts of Tejakula, Kubuaddan, Sawan, Buleleng, Sukasada, Banjar, Busungbiu, Gerokgak and Seririt, Buleleng district. Data analysis used multiple regression analysis. The results of this study state that legal protection does not affect the potential for bankruptcy of the LPD, the competence of managers variable affects the potential for bankruptcy of the LPD, the variable Good Corporate Governance does not affect the potential for bankruptcy of the LPD, the variable active role of citizens does not affect the potential for bankruptcy of the LPD, the variable The role of the internal supervisory body affects the potential for bankruptcy. LPD bankruptcy in Buleleng Regency.